Greeks - Peach, Susan; Millard, Anne.; Jackson, Ian. (New York : Scholastic, 2004)
Learning about Greek civilizations. The book looks at aspects of everyday life in ancient Greece.
Previous ed. 1990, published as "The Greeks."
11 - 12 years
Keywords: Civilization; Greece -- History; Greece -- Civilization; Greece; Juvenile works